Wariantywność stylu tekstu w perspektywie edukacyjnej - Nocoń, Jolanta (Stylistyka, 2020)
The article presents the results of an educational diagnosis. The study it describes analyses the style of invitations prepared by the Polish middle school pupils and its significant variation despite the fact that the subjects did identical tasks in identical conditions. The author is interested in the pupils’ awareness of style, which is why the study analyses only the texts whose writers have made a deliberate and conscious choice of stylistic models. The diversity of style has turned out to be the most pronounced on the level of register, and the main reason behind the style variation among the texts was rooted in the clash between opposing stylistic systems (formality vs. informality) and the overlapping of several discourses: the school, internet and colloquial discourse. The pupils have shown much creativity, choosing one of the three strategies to cope with the paradoxes of style designed by the authors of the task. None of the variants of style employed by the pupils in their invitations can be judged as incorrect or artificial. In such a situation, the basic category evaluating the style of